Work Activity Pattern and Collaboration Network: New Drivers for Workplace Space Planning and Design. Issue 3 (17th July 2022) - Tagliaro, Chiara; Zhou, Yaoyi; Hua, Ying
ABSTRACT: Information about the users' work activity patterns is essential for office space planning and the design of organizations. However, it is not clear yet what factors can be used for predicting work activities, especially at the group level. In this study, we found that work activity patterns of groups are associated with the workgroup's job function and their location in the organizational collaboration networks. Two hypotheses were tested through a survey conducted on a sample of 188 managers from an Italian utility company. The participants were asked about (1) the percentage of time different groups (based on job function and demographic composition) spent doing individual, collaborative, and mobile work; and (2) how network connectivity affected individual versus group work. The results showed that workgroups with different job functions spent different percentages of time on individual, mobile, and teamwork. Communication network connectivity is not significantly correlated with the amount of time spent on individual work, but statistical evidence confirmed that it plays an essential role for the assessment of the amount of work time spent on teamwork, even more than job functions. By investigating the factors affecting collaborations between groups, we advanced the research on work activity in large companies in order to complement existing studies that mostly addressed work activity patterns at the individual level. How information about collaboration networks can be utilized for space planning and flexible work arrangement policy‐making is also discussed, in light of the changes that the COVID‐19 pandemic has triggered.